OPTIMALISASI PERAN KOMITE SEKOLAH DALAM MENINGKATKAN PARTISIPASI MASYARAKAT - Ritmon Amala; Novianty Djafri; Pupung Puspa Ardini; Muhammad Zubaedi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This research aims to explore strategies for optimizing the role of school committees in enhancing community participation in education. The research was conducted at SMA Negeri 1 Pinogaluman using a qualitative approach, specifically an exploratory study, through the Focus Group Discussion (FGD) method. A total of 12 participants were involved in this study, consisting of principals, teachers, school committee members, parents, students, and community leaders. The results of the study show that the role of school committees has been established but remains limited to administrative functions, such as fundraising and ceremonial activities. Through data analysis, three main strategies were obtained to optimize the role of school committees, namely (1) capacity building through continuous training and mentoring, (2) increasing collaboration between schools, committees, and the community, and (3) developing transparency and accountability systems in school governance. These strategies contribute to increasing public trust, promoting participatory decision-making, and enhancing the quality of educational management. The novelty of this research lies in its contextual exploration of participatory education governance practices at the secondary school level within the local socio-cultural context, utilizing the FGD approach. Practically, the results of this study provide recommendations for policymakers and school leaders to empower school committees as strategic partners in the development of continuing education.